Improved wireless tracking for indoor sports - Hedley, M.; Sathyan, T.; Mackintosh, C. (Procedia Engineering, 2011)
Wireless tracking technology is being used in a wide range of applications including performance analysis of athletes. While GPS is commonly used in outdoor environments, there are no widely deployed solutions for indoor environments to date. Indoor sports venues are often fabricated using metal structures and cladding which create difficult radio propagation environments for localization. In this paper we present a new algorithm based on measurement of time of arrival with greatly reduced susceptibility to multipath interference. Data has been collected in an indoor netball court using the WASP localization system that we developed. Using this data we show that our algorithm is able to reliably and accurately track multiple players under conditions in which conventional localization algorithms fail.